Climate change and energy insecurity : the challenge for peace, security and development - Dodds, Felix; Higham, Andrew; Sherman, Richard (Earthscan, 2009)
Climate change is now recognised as one of the greatest challenges facing the international community and when coupled with energy production and use - the most significant contributor to climate change - and the related security problems the double threat to international security and human development is of the highest order. This wide-ranging book brings together leading thinkers from academia, government and civil society to examine and address the global insecurity and development challenges arising from the twin thrust of climate change and the energy supply crunch. Part one considers ene.